MARINE MAGNETIC ANOMALIES AS RECORDERS OF GEOMAGNETIC INTENSITY VARIATIONS - Gee J.; Schneider D.A.; Kent D.V. (My University, 1996)
In addition to providing a robust record of past geomagnetic polarity reversals, marine magnetic anomalies often show shorter wavelength variations, which may provide information on geomagnetic intensity variations within intervals of constant polarity. To evaluate this possible geomagnetic signal, we compare sea surface profiles of the Central Anomaly with synthetic profiles based on Brunhes age (0-0.78 Ma) paleointensity records derived from deep sea sediments. The similarity of the synthetic profiles and observed profiles from the ultra-fast spreading southern East Pacific Rise suggests that geomagnetic intensity variations play an important role in the magnetization of the oceanic crust. This interpretation is further supported by systematic variations in the pattern of the Central Anomaly at slower spreading ridges, which are entirely consistent with a progressively smoother record of the sediment-derived paleointensity. If the sedimentary records, as calibrated to available absolute paleointensity data, accurately record variations in dipole intensity over the Brunhes, it follows that much of the Brunhes was characterized by geomagnetic intensities lower than either the mean dipole moment for the past 10 ka or the average for the period from 0.05 to 5.0 Ma. Furthermore, the sediment paleointensity records reflect the significant increase in geomagnetic intensity, from a low of ~ 2 x 1022 Am2 near 40 ka to a peak value (11 x 1022 Am2) at ~ 3 ka, that has been well documented from absolute paleointensity determinations. We suggest that geomagnetic intensity variations may be the most important cause of the rapid changes in the source layer magnetization near the ridge crest and the resultant Central Anomaly Magnetic High.
Keywords: MAGNETIC INTENSITY; MAGNETIC ANOMALIES; PALEOMAGNETISM; MARINE SEDIMENTS; BRUNHES EPOCH